Factors Influencing the Use of Cyber Extension by Gender-Based Extensioners in Supporting Artificial Intelligence in Agriculture in NTB (Case Study of Mataram City) - Hayati Hayati (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to (1) understand the aspects that affect the use of Cyber ​​Extension, and (2) to analyze the use of Cyber ​​Extension. This study uses a descriptive approach. The object in the context of this research is field agricultural extension. The sample was then determined using a purposive sampling approach, namely the City of Mataram. Determining the number of respondents using a census technique by taking the total population of agricultural field extension agents in the city of Mataram with a total of 36 extension agents, with a total of 16 male extension agents and 20 female extension agents. The type of data collected includes qualitative data and quantitative data. originating from primary and secondary sources. In the implementation of interviews and observations were selected to collect data in the field, with the variables studied in the form of aspects that influence the use of Cyber ​​Extension and the use of Cyber ​​Extension. The data obtained were then analyzed by involving descriptive analysis with a scoring system and multiple linear regression analysis using SPSS software. The results of the study illustrate that: (1) The utilization of the Cyber ​​Extension website from the aspect of utilization as a source of information is in the high category and utilization as a medium for disseminating information is included in the low category; (2) the last education variable is an aspect that has a significant effect on increasing Cyber ​​Extension. While the variables of age, gender, income level, work experience, experience using the internet, ownership of information technology, training opportunities, perceptions, and motivation are not related to reducing the use of Cyber ​​Extension